2020
DOI: 10.1016/j.eururo.2019.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of the Nuclear-localized AR-V7 Biomarker in Circulating Tumor Cells in Improving Physician Treatment Choice in Castration-resistant Prostate Cancer

Abstract: Background-Proof of the clinical utility of a biomarker is when its use informs a management decision and improves patient outcomes relative to when it is not.Objective-To model the clinical benefit of the nuclear-localized AR-V7 test for men with progressing metastatic castration-resistant prostate cancer (mCRPC) at the second line of therapy or greater to inform the choice of an androgen receptor signaling inhibitor (ARSI) or a taxane. Design, setting, and participants-The study population was a cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 20 publications
0
58
0
Order By: Relevance
“…A report by Graf et al indicated that doctors prefer taxane to NHT for patients with a highly aggressive disease or who have received NHT previously, which might result in treatment selection tendency. After adjusting physician propensity, no marked differences in OS were observed between taxane-and NHT-treated patients (42). Elsewhere, nuclear CTC expression of AR-V7 protein was associated with better survival in mCRPC patients receiving taxane therapy than those receiving NHT (11).…”
Section: Discussionmentioning
confidence: 93%
“…A report by Graf et al indicated that doctors prefer taxane to NHT for patients with a highly aggressive disease or who have received NHT previously, which might result in treatment selection tendency. After adjusting physician propensity, no marked differences in OS were observed between taxane-and NHT-treated patients (42). Elsewhere, nuclear CTC expression of AR-V7 protein was associated with better survival in mCRPC patients receiving taxane therapy than those receiving NHT (11).…”
Section: Discussionmentioning
confidence: 93%
“…In the context of clinical studies, patients with CTCs expressing AR-V7 showed worst outcome when compared to those patients harboring AR-V7-negative CTCs or no CTCs (52). Very recently, it was demonstrated that men with metastatic PCA who were tested positive for nuclear-localized AR-V7 protein in CTCs were likely to live longer if taxane based chemotherapy was used (53). In the PROPHECY Trial, a multicenter, prospective-blinded study of men with high-risk metastatic castration resistant PCA starting abiraterone acetate or enzalutamide treatment, the detection of AR-V7 in CTCs by two assays was independently associated with shorter PFS and OS, concluding that such men should be offered alternative treatments (54).…”
Section: Discussionmentioning
confidence: 99%
“…Poorer failure free survival (but not overall survival was additionally seen in men with worse primary tumour stage and higher PSA level before starting ADT. There is overlap between these poor prognostic features and factors associated with a high likelihood of harbouring AR-V7 positive CTCs 33 40 51…”
Section: Methods and Analysismentioning
confidence: 99%